Deregulation of MADS-box transcription factor genes in a mutant defective in the WUSCHEL-LIKE HOMEOBOX gene EVERGREEN of Petunia hybrida. (3rd June 2018) - Schorderet, M.; Duvvuru Muni, R. R.; Fiebig, A.; Reinhardt, Didier
ABSTRACT: Angiosperm inflorescences develop in two fundamentally different ways. In monopodial plants, for example in Arabidopsis thaliana, the flowers are initiated as lateral appendages of a central indeterminate inflorescence meristem. In sympodial plants, flowers arise by terminal differentiation of the inflorescence meristem, while further inflorescence development proceeds from new sympodial meristems that are generated at the flank of the terminal flower. We have used the sympodial model species Petunia hybrida to investigate inflorescence development. Here, we describe a mutant, bonsai ( bns ), which is defective in flower formation, inflorescence branching, and control of meristem size. Detailed microscopic analysis revealed that bns meristems retain vegetative charateristics including spiral phyllotaxis. Consistent with a block in flower formation, bns mutants exhibit a deregulated expression of various MADS-box genes. Molecular analysis revealed that the bns mutant carries a transposon insertion in the previously described EVERGREEN ( EVG ) gene, which belongs to the WUSCHEL-LIKE HOMEOBOX ( WOX ) transcription factor gene family. EVG falls in the WOX9 subfamily, which has diverse developmental functions in angiosperms. The comparison of WOX9 orthologues in five model species for flowering shows that these genes play functionally divergent roles in monopodial and sympodial plants, indicating that the WOX9 regulatory node may have played an important role in the evolution of shoot architecture.